The Influence of Advanced Leadership Education on the Management of Pedagogical Transformation - Raymond Ndubisi Anyanwu; Sanage Anne-Marie Payet (Journal of Research in Education and Pedagogy, 2025)
While effective change management is contingent upon robust and strategic leadership, occupying a managerial position does not inherently confer the ability to lead change successfully. This study examined the effectiveness of school managers holding advanced leadership qualifications in implementing policies designed to facilitate pedagogical transformation. The study aimed to assess teachers’ policy knowledge and to determine the extent of institutional support provided for policy implementation. It is hypothesised that teachers working in schools led by managers with higher leadership credentials demonstrate greater policy knowledge and receive more professional support. Using a qualitative, descriptive, cross-sectional survey design, a semi-structured questionnaire comprising three sections - respondent demographics, policy knowledge, and support - was administered to 104 teachers from three purposively selected primary schools located on Mahé, the main island of Seychelles. Descriptive statistical techniques were applied to analyse categorical data, yielding item-response frequency percentages, while qualitative coding was used to identify emergent themes within textual data. The results indicated that while a significant number of teachers demonstrated policy knowledge deficiency, they nonetheless received adequate support, rendering the initial hypothesis only partially substantiated. Policy knowledge deficiency among teachers may result in strategic myopia, fragmented implementation of frameworks, and ultimately suboptimal outcomes. Conversely, adequate support can alleviate stress, encourage policy adoption, and contribute to improved educational attainment. This pioneering study conducted in Seychelles provides valuable insights into the impact of advanced leadership qualifications on pedagogical change management. It further presents evidence-based recommendations to address policy knowledge gaps among teachers, strengthen institutional support mechanisms, and guide future research, thereby deepening the understanding of challenges inherent in leading pedagogical transformation.